The dynamic changes of mango (Mangifera indica L.) epicuticular wax during fruit development and effect of epicuticular wax on Colletotrichum gloeosporioides invasion - Wu, Jingbo; You, Yuquan; Wu, Xiao; Liu, Feng; Li, Guoping; Yin, Hao; Gu, Chao; Qi, Kaijie; Wei, Qing; Wang, Songbiao; Yao, Quansheng; Zhan, Rulin; et al. (Frontiers in Plant Science, 2023)
Mango fruits are susceptible to diseases, such as anthracnose, during fruit development, leading to yield reduction. Epicuticular wax is closely related to resistance of plants to pathogenic bacterial invasion. In this study, the effect of mango fruit epicuticular wax on the invasion of Colletotrichum gloeosporioides was investigated, followed by to understand the changes of wax chemical composition and crystal morphology during mango fruit development using GC-MS and SEM. Results showed that the epicuticular wax of mango fruits can prevent the invasion of C. gloeosporioides, and ‘Renong’ showed the strongest resistance to C. gloeosporioides. The wax content of four mango varieties first increased and then decreased from 40 days after full bloom (DAFB) to 120 DAFB. In addition, 95 compounds were detected in the epicuticular wax of the four mango varieties at five developmental periods, in which primary alcohols, terpenoids and esters were the main wax chemical composition. Furthermore, the surface wax structure of mango fruit changed dynamically during fruit development, and irregular platelet-like crystals were the main wax structure. The present study showed the changes of wax content, chemical composition and crystal morphology during mango fruit development, and the special terpenoids (squalene, farnesyl acetate and farnesol) and dense crystal structure in the epicuticular wax of ‘Renong’ fruit may be the main reason for its stronger resistance to C. gloeosporioides than other varieties. Therefore, these results provide a reference for the follow-up study of mango fruit epicuticular wax synthesis mechanism and breeding.